2007
DOI: 10.1037/0022-0663.99.2.241
|View full text |Cite
|
Sign up to set email alerts
|

Teachers' achievement goal orientations and associations with teachers' help seeking: Examination of a novel approach to teacher motivation.

Abstract: It was proposed that achievement goal theory can be applied to conceptualizing motivation not only for learning but also for teaching. As predicted, responses of 320 teachers to a new self-report measure of goal orientations for teaching yielded 4 factors reflecting distinct mastery, ability-approach, abilityavoidance, and work-avoidance goals. Data from 212 teachers who also completed measures of help seeking confirmed that mastery goals predicted positive perceptions of help seeking, preferences for receivin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

25
398
6
59

Year Published

2011
2011
2023
2023

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 356 publications
(510 citation statements)
references
References 45 publications
25
398
6
59
Order By: Relevance
“…In research, teacher motivation has been investigated mainly in terms of self-efficacy beliefs (e.g., Dicke et al, 2014;Klassen & Chiu, 2011;Moe, Pazzaglia, & Ronconi, 2010; see also Woolfolk Hoy, Hoy, & Davis, 2009) and goal orientations (e.g., Butler, 2007Butler, , 2012Klassen, Perry, & Frenzel, 2012;Nitsche, Dickh€ auser, Fasching, & Dresel, 2011;Retelsdorf, Butler, Streblow, & Schiefele, 2010). Less often has teacher motivation been examined in terms of intrinsic motivation (see Kunter & Holzberger, 2013;Roth, 2013) or (positive) affect Keller et al, 2014;Kunter et al, 2008).…”
Section: Journal Of Research In Science Teachingmentioning
confidence: 99%
“…In research, teacher motivation has been investigated mainly in terms of self-efficacy beliefs (e.g., Dicke et al, 2014;Klassen & Chiu, 2011;Moe, Pazzaglia, & Ronconi, 2010; see also Woolfolk Hoy, Hoy, & Davis, 2009) and goal orientations (e.g., Butler, 2007Butler, , 2012Klassen, Perry, & Frenzel, 2012;Nitsche, Dickh€ auser, Fasching, & Dresel, 2011;Retelsdorf, Butler, Streblow, & Schiefele, 2010). Less often has teacher motivation been examined in terms of intrinsic motivation (see Kunter & Holzberger, 2013;Roth, 2013) or (positive) affect Keller et al, 2014;Kunter et al, 2008).…”
Section: Journal Of Research In Science Teachingmentioning
confidence: 99%
“…By their definitions, autonomy-oriented help is less instrumental in the short term than dependency-oriented help, because the recipient of help needs to contribute at least partially to solving the problem. However, in the long term, this contribution to problem solving will empower help recipients, boost confidence in their own abilities, and contribute to a sense of control (Butler, 2007;A. M. Ryan & Pintrich, 1997).…”
Section: The Psychological Costs Of Seeking Helpmentioning
confidence: 99%
“…Autonomyoriented help provides recipients with the tools to solve their problems on their own. Autonomy-oriented help is aimed at empowering the helpee and assumes that, given the appropriate tools, recipients can help themselves (Butler, 2007;Nadler, 2002;A. M. Ryan & Pintrich, 1997).…”
Section: The Psychological Costs Of Seeking Helpmentioning
confidence: 99%
“…Previously, Butler (2007) reported that there was not a significant relation between teaching competence and teachers' goal orientations. Learning goal orientations and performanceavoidance goal orientation of primary school pre-service teachers were stronger than their performanceapproach orientations (Perry, 2007).…”
Section: Discussionmentioning
confidence: 99%